Modelling Water Flow in Unsaturated Porous Media Accounting for Nonlinear Permeability and Material Heterogeneity - Szymkiewicz, Adam (GeoPlanet: Earth and Planetary Sciences, 2013)
The book focuses on two issues related to mathematical and numerical modelling of flow in unsaturated porous media. In the first part numerical solution of the governing equations is discussed, with particular emphasis on the spatial discretization of highly nonlinear permeability coefficient. The second part deals with large scale flow in heterogeneous porous media of binary structure. Upscaled models are developed and it is shown that the presence of material heterogeneities may give rise to additional non-equilibrium terms in the governing equations or to hysteresis in the averaged constitutive relationships.